Inhibition of Dendritic Cell Activation and Modulation of T Cell Polarization by the Platelet Secretome - Saris, Anno; Steuten, Juulke; Schrijver, David P.; van Schijndel, Gijs; Zwaginga, Jaap Jan; van Ham, S. Marieke; ten Brinke, Anja (Frontiers in Immunology, 2021)
Platelet transfusions are a frequently administered therapy for especially hemato-oncological patients with thrombocytopenia. Next to their primary function in hemostasis, currently there is increased attention for the capacity of platelets to affect the function of various cells of the immune system. Here, we investigate the capacity of platelets to immuno-modulate monocyte-derived dendritic cells (moDC) as well as primary dendritic cells and effects on subsequent T cell responses. Platelets significantly inhibited pro-inflammatory (IL-12, IL-6, TNF) and increased anti-inflammatory (IL-10) cytokine production of moDCs primed with toll-like receptor (TLR)-dependent and TLR-independent stimuli. Transwell assays and ultracentrifugation revealed that a soluble factor secreted by platelets, but not microvesicles, inhibited DC activation. Interestingly, platelet-derived soluble mediators also inhibited cytokine production by human ex vivo stimulated myeloid CD1c+ conventional DC2. Moreover, platelets and platelet-derived soluble mediators inhibited T cell priming and T helper differentiation towards an IFN+ Th1 phenotype by moDCs. Overall, these results show that platelets are able to inhibit the pro-inflammatory properties of DCs, and may even induce an anti-inflammatory DC phenotype, with decreased T cell priming capacity by the DC. The results of this study provide more insight in the potential role of platelets in immune modulation, especially in the context of platelet transfusions.